Interpersonal Communication Patterns and Intimate Relationship Motivation on Gay and Lesbian Dating Couple - Fajar Ramadhan, Yusuf; Lukmantoro, S.Sos, M.Si, Triyono (Interaksi Online, 2016)
Communication pattern and intimate relationship motivation become one of interpersonal relationships increasing stimulus and the success in solving interpersonal problems or conflict which threaten the relationship. Status and role division in the relationship, such as top and bottom in gay community and butchy and femme in lesbian community, give an overview of how gay and lesbian camouflaged to become couple just like how straight people do in intimate relationships. This research is a qualitative research with phenomenology-critical constructive paradigm which focus on communication pattern and intimate relationship motivation and gay and lesbian dating couples that domiciled in Semarang City as the research subject. Refers to Joseph DeVito communication pattern and Baxter & Montgomerry praxis patterns theory, this research reveals how gay and lesbian use correct communication pattern to build relationship on the basis of the same gander and conflict resolution in their relationships. The usage of Duvall & Miller intimate relationship theory shows that the highest motivation of gay and lesbian to build a relationship is based on status and role which was explained in Queer theory from Judith Butler. The result shows that gay couples communications are dominated by the reverse balance pattern. Meanwhile, lesbians are more dominated by the balance pattern. Gays intimate relationships motivations are more than socialization, sexual needs, and entertainment mediums, different from lesbians who are more likely to avoid social criticism and searching for partner. Praxis patterns functionalist on balance category is more preffered by gays as the problem solving method, while lesbians are more preffers on spiraling alternation category. This communication pattern and intimate relationship motivation cannot be separated from status and role frame which are played in relationship with their partner, whether top or bottom for gay, and butchy or femme for lesbian. The pattern of gay couples more open communication both on the couple or the environment than a lesbian couple, it is influenced by the presence of several reasons like social sanction and family pride motivates gay and lesbian couples to establish intimate relationships. Lesbian couples assume that the boyfriend who is a girl is a person who is able to understand her well.